Voice Giving (Way) - Milner, Laura A. (Disability Studies Quarterly, 2011)
This feminist, embodied narrative explores the shame, blame, and desire that accompany a professor's diagnosis of disabled body and speech and the paradoxical importance and near impossibility of reclaiming her voice. The writer resists the traditional story arc and avoids the rhetorical patterns of triumph, horror, conversion, and nostalgia found in many disability narratives. Aiming for what Couser (2008) calls a "rhetoric of emancipation," she challenges stereotypical attitudes toward women with chronic fatigue immune dysfunction syndrome (CFIDS) by offering "testimonio," a politicized narrative of growth and transformation that connects with and advocates for, in this case, CFIDS sufferers and sexual abuse survivors. She describes how writing her experience of disabling illness for publication has enabled her to testify in court on behalf of others who suffer in silence and has led to a more peaceful way of being, rather than always doing---a necessary shift for those who navigate daily the conflict between participating fully and resting enough to avoid serious relapse.